Variation of Slab Component in Ancient and Modern Merapi Products: A Detailed Look into Slab Derived Fluid Fluctuation over the Living Span of One of the Most Active Volcanoes in Sunda Arc - Esti Handini; Toshiaki Hasenaka; Agung Harijoko; Yasushi Mori (Geological Engineering Department Universitas Gadjah Mada, 2017)
Holocene eruptions of Merapi have produced both medium-K and high-K calc alkaline series which correspond to products older and younger than 1900 years respectively. The change has been attributed to increasing sediment input as the volcano matures. This study presents two Merapi samples which represent Ancient and Modern Merapi. The two samples are analyzed for subduction components including B, Ba, Sr, and Pb using X-ray ﬂuorescence (XRF) spectrometer and prompt gamma ray analysis (PGA). Our ﬁnding shows that Ancient Merapi sample from Plawangan Hill lava is close in afﬁnities with younger than 1900 years high-K magma series. On the other hand, Modern Merapi sample from 2006 eruption juvenile is plotted within medium-K magma series which are observed in eruption products older than 1900 years. Ratios of ﬂuid mobile elements to high ﬁeld strength element (HFSE) (i.e. B/Nb, Ba/Y, Pb/Nb) consistently show that Ancient Merapi sample has higher input of slab derived ﬂuid than Modern Merapi sample. A model using B/Nb and Ba/Nb suggests that Plawangan magma requires 1.5 % of sediment derived ﬂuid, higher than estimated in 2006 eruption magma (1.2 %) and medium-K series magma, and within the range of high-K series magma, to explain its slab component enrichment. This evidence suggests that slab derived component addition to the sub-arc mantle wedge highly ﬂuctuates over short period of evolution of a volcano. One possible explanation is the presence of veined hydrous metasomatized sub-arc mantle as Merapi magma source which allows melting of different mantle area to produce ﬂuctuation of slab components in the course of evolution of Merapi magmas.